Application of Contextual Architecture Approach in the Redesign of Type B Bus Terminal in Binjai City - Shela Ocvia; mufti ali nasution (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2026)
Bus terminals are essential land transportation hubs that support community mobility and serve as public facilities that often act as the first point of arrival. Beyond accommodating transport activities, terminals reflect an area's identity. The Type B Bus Terminal in Binjai City is strategically located adjacent to the Binjai Railway Station, a historic building and vital transportation node. However, the existing terminal's condition is suboptimal regarding functionality, user comfort, and spatial quality. Crucially, it lacks a visual character that harmonizes with the station, the area's dominant architectural element. This study aims to apply a contextual architectural approach to redesign the terminal, producing a building capable of responding to its environment through visual harmony. Employing a descriptive qualitative method, data was collected via field observations, documentation, literature reviews, and site analysis. The findings indicate that the railway station possesses a distinct architectural character: symmetrical massing, rhythmic arch elements along corridors, louvered façades, and neutral colors. Based on these findings, Brent C. Brolin’s harmony strategy was selected. This approach was implemented by adapting the terminal’s mass composition to the station's pattern, incorporating arched elements in pedestrian corridors, utilizing louvered secondary skins, and adapting the color scheme without literal imitation. The resulting design demonstrates that the contextual architecture approach successfully creates a terminal visually aligned with the railway station. It strengthens the area's identity and maintains its core function as an integrated public transportation facility.